Giant Cell Tumor of the Patellar Tendon Sheath: A Rare Case of Anterior Knee Pain - Kılıçaslan, Ömer Faruk (Cureus, 2017)
Giant cell tumor of the tendon sheath (GCTTS) is a benign, proliferative lesion of the synovium of the joint, the bursa, and the tendon sheath. We report a case of intra-articular, localized GCTTS arising from the patellar tendon, which is a rare cause of anterior knee pain. The diagnosis may be delayed due to non-specific symptoms and normal plain radiographic findings. Magnetic resonance imaging (MRI) is diagnostic to detect the lesion, but several other clinical entities and lesions should be evaluated in the differential diagnosis. The treatment of choice is a total excision of the lesion without leaving residual tumor tissue, in order to reduce the risk of recurrence. We present a patient with GCTTS of the patellar tendon and discuss its clinical and radiographic characteristics, differential diagnosis, pathology, and treatment.